We were given the equation for Ann's candies, which is as follows:
![A=2S-3](https://img.qammunity.org/2023/formulas/mathematics/high-school/xngw1fyo95paxp74dkio9doaneh57by514.png)
To solve it for Susan we have to isolate the "S" variable on the left side. This is done by changing the other terms from one side to the other, when we do that their operation gets switched to its inverse. With this in mind let's solve the equation:
![\begin{gathered} A=2S-3 \\ (-2s=-3-A)\cdot-1 \\ 2s=3+A \\ s=(3)/(2)+(A)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/hgwwd81ntoagpw7pk829cb7j6wmh3w4uss.png)
The equation for susan is S = 3/2 + A/2.